Enhancing Educational Quality Through Internal Quality Assurance Systems in Indonesian Primary and Secondary Schools - DIOP, Mouhamed (Journal of Educational Research and Policies, 2025)
This study discusses the Internal Quality Assurance System (SPMI) in primary and secondary education units in Indonesia. SPMI is an independent education quality assurance system aimed at fostering a culture of quality in a sustainable manner. The implementation of SPMI refers to the National Education Standards (SNP) and covers all aspects of education implementation. This study explains the SPMI cycle, the duties of education units in quality assurance, SPMI principles, and quality assurance success measures which include output, outcome, and impact indicators. The success of SPMI is supported by management commitment, continuous improvement, orientation on service user satisfaction, active involvement of educators and education personnel, training, communication, cooperation, and support from the local government. With the effective implementation of SPMI, it is hoped that the quality of education in educational units can improve continuously and equitably.